ASSISTANCE TO THE UNEMPLOYED IN EMPLOYMENT IN THE NEIGHBORHOOD: GUARANTEE AND OPPORTUNITIES (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The study examined increasing the level of employment and income of residents of the neighborhood, based on the characteristics of the neighborhood, using available opportunities. Specific aspects of international experience in increasing the level of employment of the population have been studied based on territorial units, characteristics and existing legal and other opportunities. The article also discusses the development of rural and urban neighborhood, mitigation and elimination of factors that negatively affect the level of employment of the population, reforms aimed at increasing the incomes of the neighborhood population, relevant indicators and theoretical and scientific foundations.
Keywords: neighborhood, neighborhood system, employment in neighborhoods, development of neighborhoods, opportunities to increase employment of the population, vocational training of the unemployed, system of qualifications and advanced training, employers in neighborhoods, improvement of labor relations in neighborhoods.